Variability in rates of coastal change along the Yukon Coast, 1951 to 2015 - Irrgang, Anna Maria (Dr.); Lantuit, Hugues (Prof. Dr.); Manson, Gavin K.; Günther, Frank (Dr.); Grosse, Guido (Prof. Dr.); Overduin, Pier Paul (Journal of Geophysical Research: Earth Surface, 2018)
To better understand the reaction of Arctic coasts to increasing environmental pressure, coastal changes along a 210-km length of the Yukon Territory coast in north-west Canada were investigated. Shoreline positions were acquired from aerial and satellite images between 1951 and 2011. Shoreline change rates were calculated for multiple time periods along the entire coast and at six key sites. Additionally, Differential Global Positioning System (DGPS) measurements of shoreline positions from seven field sites were used to analyze coastal dynamics from 1991 to 2015 at higher spatial resolution. The whole coast has a consistent, spatially averaged mean rate of shoreline change of 0.7 +/- 0.2 m/a with a general trend of decreasing erosion from west to east. Additional data from six key sites shows that the mean shoreline change rate decreased from -1.3 +/- 0.8 (1950s-1970s) to -0.5 +/- 0.6 m/a (1970s-1990s). This was followed by a significant increase in shoreline change to -1.3 +/- 0.3 m/a in the 1990s to 2011. This increase is confirmed by DGPS measurements that indicate increased erosion rates at local rates up to -8.9 m/a since 2006. Ground surveys and observations with remote sensing data indicate that the current rate of shoreline retreat along some parts of the Yukon coast is higher than at any time before in the 64-year-long observation record. Enhanced availability of material in turn might favor the buildup of gravel features, which have been growing in extent throughout the last six decades. Plain Language Summary The Arctic is warming, but the impacts on its coasts are not well documented. To better understand the reaction of Arctic coasts to increasing environmental pressure, shoreline position changes along a 210-km length of the Yukon Territory coast in northwest Canada were investigated for the time period from 1951 to 2015. Shoreline positions were extracted from historical aerial images from the 1950s, 1970s, and 1990s and from satellite images from 2011. Additionally, measurements of shoreline ...